Effectiveness Music Therapy On Hemodialysis Patients: Scooping Review - Nurul Hidayah; Anja Hesnia Kholis; Ratna Puji Priyanti; Novita Surya Putri; Siswati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Background: Music can provide relaxation to the listener and it has become a therapeutic effect. Listening to music during hemodialysis sessions can induce blood pressure, heart rate, respiratory rate, temperature changes, and serum free fatty acids which have beneficial effects on the body's metabolism Aims: to evaluate the effectiveness music therapy to patients undergoing hemodialysis. Design: Search articles using Scopus, Science Direct, PubMed, and Springer link. Articles identified using keywords music AND (therapy or interaction) AND hemodialysis published on 2014 -2018 and found 112 articles. Results: All articles were reviewed using a randomized controlled trial (RCT) design by reviewing the parameters of anxiety, depression, sleep quality, pain level, and vital parameters of music therapy intervention. Conclusion: music therapy has a significant effect when measured by parameters of anxiety, depression, sleep quality, pain level, vital parameters.